Implementasi Program BERGEMA BOSS (Bergerak Bersama Baturetno Atasi Stunting) di Kalurahan Baturetno - Sofani; Nur Fitri Mutmainah (Jurnal Ilmiah Administrasi Publik, 2026)
The stunting rate in children under five in Indonesia is still relatively high. Baturetno Village is one of the villages in the Bantul Regency area, which is concerned about the stunting program.  This study analyzes the implementation of the BERGEMA BOSS PMT program in Baturetno Village, Bantul Regency, as an effort to reduce stunting rates. The research methodology uses qualitative research with a descriptive approach. Based on the analysis of Edwards III's model theory (communication, resources, disposition, bureaucratic structure), this study found that the BERGEMA BOSS program was very effective.  One of the keys to the success of the BERGEMA BOSS program is clear communication, adequate human and financial resources, a positive implementing disposition, and a conducive bureaucratic structure. Despite minor operational challenges, the program has succeeded in reducing stunting rates. The conclusion of this study shows that the implementation of procedures and supported by collaboration, innovation, and full support for implementers is an essential factor in the success of this program in reducing stunting rates.